2019
DOI: 10.4103/ua.ua_192_17
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of bladder tumor antigen quantitative test in the diagnosis of bladder carcinoma in a schistosoma endemic area

Abstract: Introduction: Bladder carcinoma is the most common male cancer in our environment due to endemicity of schistosomiasis. Squamous-cell carcinoma is the most common histological type and patients present at an advanced stage. The objective of this study is to compare the sensitivity, specificity, and predictive values of the bladder tumor antigen quantitative test (BTA TRAK) and urine cytology in the diagnosis of bladder carcinoma in a schistosoma endemic area. Materials and Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…However, there is no new consensus indicator on the risk factors for the recurrence of NMIBC, especially the lack of relevant tumor indicators in urine. Urine BLCA-4, BTA, NMP22, and CEA can be used as important markers for the diagnosis and recurrence monitoring of bladder cancer [23][24][25][26][27][28][29][30]. At present, the specificity and sensitivity of BLCA-4 detection for bladder cancer diagnosis have reached a high level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is no new consensus indicator on the risk factors for the recurrence of NMIBC, especially the lack of relevant tumor indicators in urine. Urine BLCA-4, BTA, NMP22, and CEA can be used as important markers for the diagnosis and recurrence monitoring of bladder cancer [23][24][25][26][27][28][29][30]. At present, the specificity and sensitivity of BLCA-4 detection for bladder cancer diagnosis have reached a high level.…”
Section: Discussionmentioning
confidence: 99%
“…Zhao et al [24] retrospective analysis of 325 patients with bladder cancer confirmed that the 5-year recurrence-free survival rate of patients with low expression of tumor tissue BLCA-4 was 89.8%. BTA, also known as complement factor H-related proteins, can interfere with the complement pathway, allowing tumor cells to evade the immune system and produce tumors [25]. Bladder tumor is in contact with the basement membrane of the bladder.…”
Section: Discussionmentioning
confidence: 99%
“…They reported no association between BWT and BTA and lower urinary tract symptoms, and suggested that the role of urogenital schistosomiasis in urinary BTA levels needed to be explored further. Meanwhile, the study by Muhammad et al looked at the role of a quantitative test (BTA TRAK) compared with urine cytology in the diagnosis of BC in the schistosoma endemic area of Sokoto 29. The authors concluded that BTA TRAK is less specific than urine cytology, but is more sensitive for detecting BC in the area of investigation.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, the study by Muhammad et al looked at the role of a quantitative test (BTA TRAK) compared with urine cytology in the diagnosis of BC in the schistosoma endemic area of Sokoto. 29 The authors concluded that BTA TRAK is less specific than urine cytology, but is more sensitive for detecting BC in the area of investigation. The study by Onile et al differed in that they identified several parasite-specific and host-specific protein biomarkers for the detection of schistosomiasis.…”
Section: Open Accessmentioning
confidence: 99%
See 1 more Smart Citation